Rescuing the Hyperventilation theory of Panic Reply to Ley (2005). [article]. - Roth, Walton T.
In his comment on W. T. Roth, F. H. Wilhelm and D. Pettit (2005) R. Ley (2005) argued that the authors erred in evaluating the basic, simple hyperventilation theory of panic rather than his theory, which is based on "complex physiological and psychological principles" (p 197). Indeed, Roth et al may have overestimated the heuristic value of the basic theory by counting citations to Ley's (1985) article. Furthermore, Roth et al's conclusion that the basic is falsifiable may not be valid fo Ley's theory, which makes categorical distinctions whose application is uncertain. Yet, the authors of the present article maintain the hope that a more nuanced but falsifiable multifactorial respiratory theory can be developed with more explanatory power than that of the basic theory. The relative truth or falsity of such a theory could be expressed in statistical terms. -- (from the author)